Cholesterol-dependent amyloid β production: space for multifarious interactions between amyloid precursor protein, secretases, and cholesterol - Rudajev, Vladimir; Novotny, Jiri (Cell & bioscience, 2023)
Amyloid β is considered a key player in the development and progression of Alzheimer's disease (AD). Many studies investigating the effect of statins on lowering cholesterol suggest that there may be a link between cholesterol levels and AD pathology. Since cholesterol is one of the most abundant lipid molecules, especially in brain tissue, it affects most membrane-related processes, including the formation of the most dangerous form of amyloid β, Aβ42. The entire Aβ production system, which includes the amyloid precursor protein (APP), β-secretase, and the complex of γ-secretase, is highly dependent on membrane cholesterol content. Moreover, cholesterol can affect amyloidogenesis in many ways. Cholesterol influences the stability and activity of secretases, but also dictates their partitioning into specific cellular compartments and cholesterol-enriched lipid rafts, where the amyloidogenic machinery is predominantly localized. The most complicated relationships have been found in the interaction between cholesterol and APP, where cholesterol affects not only APP localization but also the precise character of APP dimerization and APP processing by γ-secretase, which is important for the production of Aβ of different lengths. In this review, we describe the intricate web of interdependence between cellular cholesterol levels, cholesterol membrane distribution, and cholesterol-dependent production of Aβ, the major player in AD.
Keywords: Amyloid β; Amyloid precursor protein; Amyloidogenesis; Secretase; Cholesterol